What Physiotherapists Specialized in Orthopedic Manual Therapy Know About Nocebo-Related Effects and Contextual Factors: Findings From a National Survey - Rossettini, Giacomo; Geri, Tommaso; Palese, Alvisa; Marzaro, Chiara; Mirandola, Mattia; Colloca, Luana; Fiorio, Mirta; Turolla, Andrea; Manoni, Mattia; Testa, Marco (Frontiers in Psychology, 2020)
Objective: Thus, the aim of this study was to investigate the knowledge of orthopaedic manual therapists (OMTs) regarding context factors (CFs) capable of triggering nocebo effects during the treatment and how this knowledge is related to their socio-demographic features. Design: A cross-sectional online survey. Setting: National. Main outcome measures: A 20 items questionnaire composed by open-ended and closed single-choice questions was administered to explore: (a) socio-demographic variables (10 questions); (b) the relation between different CFs and nocebo-related effects (2 questions); and (c) the knowledge of participants about nocebo-related effects and how they managed them in the clinical practice (8 questions). Participants: 1288 OMTs from the database of the Master in Rehabilitation of Musculoskeletal Disorders (MRDM) of the University of Genova from March to May 2019. Inclusion criteria were: (a) to possess a valid email account; (b) to understand and use as a native language the Italian; (c) to be graduated as OMTs; and (d) to be employed as physiotherapists specialized-OMTs during the survey. Results: 791 responses were received (61.4%); 473 of them were male (59.8%), with an average age of 31.0 ± 7.1 years. OMTs defined nocebo-related effects as the psychosocial context effects around therapy and patient with specific biological bases (72.2%). OMTs know that their clinical practice is pervaded by nocebo-related effects (42.5%), triggered by CFs. Participants communicated nocebo-related effects balancing the positive features of the therapy with the negative ones (50.9%), during the decision of the therapeutic plan (42.7%). They reported associative learning as the main mechanism involved in nocebo-related effects (28.8%). OMTs taught and trained patient’s strategies to manage nocebo-related effects (39.6%) through an evaluation and correction of patient’s anxieties, doubts and expectations (37.7%). OMTs most frequently considered themselves to have a “medium” education about nocebo-related effects (48.2%) and that their management should be taught during bachelor (78.6%). Conclusion: OMTs believed that nocebo-related effects were present in their clinical practice and that they can be triggered by CFs.